Notes on Indian Neolitsea (Lauraceae)—two new varietal combinations under N. cassia and N. foliosa and typification of five names - Chakrabarty, Tapas (Phytotaxa, 2019)
During the course of revision of the genus Neolitsea (Bentham 1880: 161) Merrill (1906: 56) for India and adjoining countries it was found that N. foliosa (Nees 1831: 64) Gamble (1925a: 1240) and N. cassia (Linnaeus 1753: 369) Kostermans (1952: 85) are two closely related species, the former differing from the latter “by having much broader, coriaceous leaves with a pronounced areolation, the completely glabrous terminal buds and branches, and the glabrous outer bud scales of the flower umbels.” (Kostermans 1995: 169). Further, both these species have two types of fruits, mostly globose to subglobose but occasionally oblong, oblong-ellipsoid to ovoid-oblong. The present study revealed that these two forms of fruits merit recognition as distinct varieties in each species, having no intergradations. The variety of N. cassia, characterized by such oblong fruits has been described previously as Litsea zeylanica (Nees & T. Nees 1823: 58, pl. 5) var. rigescens Meissner (1864: 226), which therefore is transferred to N. cassia here with designation of a lectotype. In N. foliosa, an isolectotype (G00694474: image!) bears oblong to oblong-ellipsoid fruits but the common form with globose to subglobose fruits has been described previously as Litsea scrobiculata (Meissner 1864: 223), treated in Indian Floras (e.g. Gamble 1925a, Saldanha & Ramesh 1984, Vajravelu 1990, Mohanan & Henry 1994) as Neolitsea scrobiculata (Meisn.) Gamble (1925a: 1240), eventually reduced to a synonym of N. foliosa by Kostermans (1995: 168–169). Hence Litsea scrobiculata is reinstated here and treated as a distinct variety of N. foliosa with designation of a lecotype. Furthermore, lectotypes are also designated for the names Tetradenia foliosa Nees (1831: 64), basionym of Neolitsea foliosa, N. fischeri Gamble (1925b: 132) and Tetradenia umbrosa Nees (1831: 64), basionym of Neolitsea umbrosa (Nees) Gamble (1914: 79).